(untitled) (Panauti Journal, 2025)
Nepal’s agricultural sector, central to rural livelihoods, is shaped by structural underdevelopment and economic dependency, influenced by imports, remittances, and migration. This study examines the relationships and combined impact of these factors on agriculture’s contribution to GDP using 25 years of secondary data (2000–2024) from the World Bank, analyzed through correlation and regression in SPSS 25. Findings highlight the negative influence of imports and remittances, reflecting Nepal’s core periphery economic structure, while migration shows minimal direct effect. The results underscore how reliance on external flows perpetuates rural marginalization and limits sectoral growth. The study emphasizes the need for policies that strengthen domestic agriculture, reduce external dependency, and promote sustainable, inclusive rural development, ensuring that growth translates into broader structural transformation.